Medicinal Ethnobotany and Potential of Medicine Plants of Anak Rawa Ethnic at The Penyengat Village Sungai Apit Siak Riau - Revina Dwi Utami; Ervizal A. M. Zuhud; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Anak Rawa ethnic is indigenous ethnic in the Penyengat Village which is located on the edge of swamp river and forest, so their dependence and adaptation to forest resources is very high. They uses the forest to make medicine plants. The objective of this research was to identify the ethnobotanical knowledge of Anak Rawa ethnic about medicine plant and identify potential species of medicine plants. The research was conducted in March to April 2018 The potential of plant data was obtained through quantitative methods in the form of vegetation and exploration analysis. Meanwhile, the community knowledge data collected through semi-structured interviews. The research identified 194 medicinal plant species at Penyengat village in several types of habitat (forests, yards, gardens, and roadsides), with 140 medicinal plant species used by Anak Rawa ethnic. There were 54 species of medicinal plants potential in Penyengat Village. Medicine plants used by the community are grouped into 28 medicinal benefits. The most widely used medicinal plants in society are in the Rubiaceae family of 11 species. Keywords: Anak Rawa ethnic, ethnobotany, medicinal plant, potential